S Q E D (4) and Q E D (4) on the Null-Plane - Casana, R.; Pimentel, B. M. [UNESP]; Zambrano, G. E. R. (Springer, 2014)
We study the scalar electrodynamics (S Q E D (4)) and the spinor electrodynamics (Q E D (4)) in the null-plane formalism. We follow Dirac's technique for constrained systems to analyze the constraint structure in both theories in detail. We impose the appropriate boundary conditions on the fields to fix the hidden subset first class constraints that generate improper gauge transformations and obtain a unique inverse of the second-class constraint matrix. Finally, choosing the null-plane gauge condition, we determine the generalized Dirac brackets of the independent dynamical variables, which via the correspondence principle give the (anti)-commutators for posterior quantization.
Keywords: Null-plane coordinates; Constraint analysis; Null-plane gauge; Dirac brackets